2019
DOI: 10.1038/s41556-019-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

CD9 identifies pancreatic cancer stem cells and modulates glutamine metabolism to fuel tumour growth

Abstract: Pancreatic ductal adenocarcinoma (PDAC) shows great cellular heterogeneity, with pronounced epithelial and mesenchymal cancer cell populations. However, the cellular hierarchy underlying PDAC cell diversity is unknown. Here we identify the tetraspanin CD9 as a marker of PDAC tumour-initiating cells. CD9 high cells had increased organoid formation capability, and generated tumour grafts in vivo at limiting dilutions. Tumours initiated from CD9 high cells recapitulated the cellular heterogeneity of primary PDAC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 71 publications
4
100
0
Order By: Relevance
“…To nd a more speci c marker of AML LSCs, we analyzed three RNA-sequencing data of LSCs and an AML MRD microarray data. From which we chose CD9, the most intensively upregulated membrane molecule, as a candidate marker for AML LSCs, which has been reported to be involved in several types of CSCs, including pancreatic cancer stem cells, breast cancer stem cells, ovarian cancer stem cells, glioblastoma stem cells, LSCs in B-acute lymphoblastic leukemia [15,20,22,[45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To nd a more speci c marker of AML LSCs, we analyzed three RNA-sequencing data of LSCs and an AML MRD microarray data. From which we chose CD9, the most intensively upregulated membrane molecule, as a candidate marker for AML LSCs, which has been reported to be involved in several types of CSCs, including pancreatic cancer stem cells, breast cancer stem cells, ovarian cancer stem cells, glioblastoma stem cells, LSCs in B-acute lymphoblastic leukemia [15,20,22,[45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that CD9 plays an important role in cell adhesion, movement, differentiation, proliferation, apoptosis and resistance [15][16][17][18][19]. Although CD9 has been reported to identify cancer stem cells in several types of cancers including pancreatic cancer, glioblastoma and B-acute lymphoblastic leukemia, and is related to the prognosis of AML, biological characteristic and regulatory mechanism of CD9 + AML LSCs remain elucidated [15,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model targeting the CK19 ductal population to induce PDAC, a population of cells highly expressive of the tetraspanin CD9 were found in the early stages of tumorigenesis. 147 The level of CD9 expression affected the ability of these cells to form organoids and initiate new tumours, and functionally CD9 interacted with the glutamine transporter ASCT2 to enhance glutamine uptake. Tuft cells, identified by the expression of Dclk1, are another cell type to emerge early in the tumorigenic process in GEMMs, and, like gastrointestinal tuft cells, possessed numerous bundles of microtubules and abundant apical cilia.…”
Section: Alisonmentioning
confidence: 99%
“…Nonetheless, so far their identification and targeting has been difficult due to the lack of specific markers. The recent publication by Wang et al [45] identified the tetraspanin CD9 as a CSC marker for PDAC. Interestingly, CD9 had previously been identified as a CSC marker in glioblastoma [46] and B-cell acute lymphoblastic leukemia [47].…”
Section: Highlighed By M Helena Vasconcelosmentioning
confidence: 99%